Literary Cincinnati the missing chapter - Brown, Dale Patrick (Ohio University Press, 2011)
"The history of Cincinnati runs much deeper than the stories of hogs that once roamed downtown streets. In addition to hosting the nation's first professional baseball team, the Tall Stacks river boating, and the May Festival, there's another side to the city--one that includes some of the most famous names and organizations in American letters. Literary Cincinnati fills in this missing chapter, taking the reader on a joyous ride with some of the great literary personalities who have shaped life in the Queen City. Meet the young Samuel Clemens working in a local print shop, Fanny Trollope struggling to open her bizarre bazaar, Sinclair Lewis researching Babbitt, hairdresser Eliza Potter telling the secrets of her rich clientele, and many more who defined the nineteenth- and early twentieth-century Queen City. For lovers of literature everywhere--but especially in Cincinnati--this is a literary tour that will entertain, inform, and amuse. "--